Experimental determination of temperature-dependent thermal conductivity of solid eicosane-based silver nanostructure-enhanced phase change materials for thermal energy storage. (April 2017) - Al Ghossein, Rabih M.; Hossain, Mohammad Sharif; Khodadadi, J.M.
Highlights: Thermal conductivity of eicosane-based phase change materials was enhanced by suspending silver nanoparticles. Three different solidification routes, namely ice-water bath, room temperature and oven solidification were tested. The oven solidification route samples exhibited the highest values while the ice-water samples showed the least increase. For loadings greater than 2 wt%, thermal conductivity varied non-monotonically with weight fraction of nanoparticles. A decrease in the latent heat and the melting point of the samples was observed as the additives loading increased. Abstract: Thermal conductivity of eicosane-based phase change materials was enhanced by suspending highly-conductive silver nanoparticles. Three batches of solid eicosane-silver samples with mass fractions (0, 1, 2, 3.5, 5, 6.5, 8 and 10 wt%) of nanoparticles were obtained under three different solidification routes: ice-water bath, room temperature and oven solidification. The transient plane source technique was used to measure the thermal conductivity at different temperatures starting at 10 °C and ending close to the melting point of each sample. Results showed an increase in the value of thermal conductivity as the temperature increased, and when close to melting point, a sharp rise in thermal conductivity was observed. Also, the slowly-prepared oven solidification route samples exhibited the highest thermal conductivity values while the ice-water samples that were prepared quickly showed the least increase. For samples with an additive loading greater than 2 wt%, a non-monotonic relationship was obtained between the thermal conductivity and the weight fraction of Ag nanoparticles, regardless of the method of solidification. In addition to thermal conductivity measurement, the latent heat of fusion of the samples was investigated, utilizing differential scanning calorimetry. Results exhibited a decrease in the latent heat and the melting point of the samples as the additives loading increased due to the decrease in the number of molecules of eicosane in the samples.